Optimasi Kinerja Jaringan WLAN Berdasarkan Analisis QoS dan Strategi - Retno, Dwi; Aini, Syarifah; Apriansyah, Apriansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Wireless LAN (WLAN) network at the Air Limau Village Office faces operational challenges in the form of connection slowdowns during high loads, dependence on primary devices, and weak security protocols. This study aims to optimize the performance of the WLAN network and improve its security and performance. The method used is a SWOT analysis to map strategic factors and network measurement using the QoS (Quality of Service) method. The QoS test results show that the network performance is mostly in the